CXCL12 as a Metastasis Inducer Chemokine of Breast Cancer - A. Altimmime, Baqir; A. Rashid, Farah (Al-Nahrain Journal of Science, 2024)
Breast cancer is a worrying challenge nowadays because it represents the most common type of cancer that has been diagnosed in women. Breast cancer deaths mainly result from metastasis instead of primary tumor. C-X-C motif chemokine ligand 12 is a chemokine that belongs to CXC group and has chemotaxis property that makes it able to migrate immune cells. Based on several studies, C-X-C motif chemokine ligand 12 and its receptor C-X-C chemokine receptor type 4 could promote breast cancer metastasis. Breast cancer metastasis is a multistep process in which the C-X-C motif chemokine ligand 12 / C-X-C chemokine receptor type 4 axis has been shown to play a key role in each of these steps such as local invasion, survival, angiogenesis, trafficking to another organ, and adaption to a new microenvironment. Many types of research have proved the crucial role of C-X-C motif chemokine ligand 12 / C-X-C chemokine receptor type 4 axis in breast cancer metastasis into the liver, bone, lung, and brain. Both in vitro and in vivo studies have provided significant results associated with the reduction of breast cancer metastasis in cell lines when they were treated with antibodies against C-X-C chemokine receptor type 4. Additionally, C-X-C motif chemokine ligand 12 / C-X-C chemokine receptor type 4 axis has provided the ability for cancer cells to resist chemotherapy, radiotherapy, and endocrine therapy. This review aims to discuss the investigations about the role of these peptides that will help in the management of a more specific and effective therapy.